Website-based Gray Literature Collection Management Darmajaya Repository: Case Study at IIB Darmajaya Library UPT - Putri, Alviarana Tsamarah Utami; Riady, Yasir (LADU: Journal of Languages and Education, 2024)
Background: College libraries not only provide printed collections such as books for lecture materials, but some of them provide collections not published to the public, usually called Gray Literature. The Gray Literature Collection is one of the main factors to consider when assessing a university library. The Gray Literature Collection contains various research results that the library/user needs. The Repository is an archival storage place designed to collect, preserve, and disseminate digital copies, especially the Darmajaya Repository Gray Literature Collection.. Purpose: This research aims to describe how the Repository is managed at the IIB Darmajaya Library and the obstacles librarians face during the management stage. Design and methods: This research uses a qualitative descriptive method using case study research. Data collection uses observation and interviews. Data analysis in this research includes data reduction, data presentation, and conclusion, while a triangulation approach is used to measure validity. Results: Based on the findings of this research, Repository management at the IIB Darmajaya Library is carried out by determining management policies, preparing hardware and software, Human Resources, and procedures for receiving collections. The final stage is uploading files into the Darmajaya Repository system. Problems are faced in managing the Darmajaya Repository because it is still in the development process, so there are still areas for improvement in management, implementation, and presentation.